2002
DOI: 10.1002/mus.10207
|View full text |Cite
|
Sign up to set email alerts
|

Predictive power of motor unit potential parameters in anal sphincter electromyography

Abstract: The diagnostic utility of motor unit potential (MUP) parameters is usually based exclusively on their diagnostic sensitivity, disregarding specificity. In the present study, advanced statistical methods were used to determine MUP parameters with the highest predictive power for the separation of neuropathic and normal external anal sphincter (EAS) muscles. Using multi-MUP analysis, 3,720 MUPs from 138 muscles of 52 patients with cauda equina lesion and 2,526 from 112 muscles of 64 controls were obtained. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
31
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 15 publications
6
31
4
Order By: Relevance
“…The sensitivities obtained with three MUP parameters (MUP thickness, duration, and number of phases), which were previously claimed to be most useful in myopathies, 7,10 were higher than those obtained with the three MUP parameters (MUP area, duration, and number of turns) most useful in neuropathic sphincter muscles. 17,18 The present study thus confirmed our previous notion that no uniform pattern of MUP parameters is optimal in all muscles and conditions. 15,17 In the present study, in both the biceps brachii and vastus lateralis muscles, we were able to identify a set of three MUP parameters (thickness and amplitude in both muscles, duration in the biceps brachii, and area or size index in the vastus lateralis) that provided the same sensitivity as all eight MUP parameters.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The sensitivities obtained with three MUP parameters (MUP thickness, duration, and number of phases), which were previously claimed to be most useful in myopathies, 7,10 were higher than those obtained with the three MUP parameters (MUP area, duration, and number of turns) most useful in neuropathic sphincter muscles. 17,18 The present study thus confirmed our previous notion that no uniform pattern of MUP parameters is optimal in all muscles and conditions. 15,17 In the present study, in both the biceps brachii and vastus lateralis muscles, we were able to identify a set of three MUP parameters (thickness and amplitude in both muscles, duration in the biceps brachii, and area or size index in the vastus lateralis) that provided the same sensitivity as all eight MUP parameters.…”
Section: Discussionsupporting
confidence: 92%
“…17,18 The present study thus confirmed our previous notion that no uniform pattern of MUP parameters is optimal in all muscles and conditions. 15,17 In the present study, in both the biceps brachii and vastus lateralis muscles, we were able to identify a set of three MUP parameters (thickness and amplitude in both muscles, duration in the biceps brachii, and area or size index in the vastus lateralis) that provided the same sensitivity as all eight MUP parameters. This points to an even higher correlation between MUP parameters in myopathy than neuropathy; in neuropathy, six MUP parameters were needed to obtain the same sensitivity as all eight MUP parameters.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…14,16 It is probably useful to apply both mean values and outlier criteria because they are complementary, with mean values disclosing diffuse, and outliers, focal pathology. 11,18 For the external anal sphincter (EAS) muscle, normative values of MUP parameters useful in quantitative EMG, 16 as well as an optimal set of MUP parameters for detection of muscle abnormality, 11 have been defined. However, the optimal diagnostic criteria for the diagnosis of neuropathic conditions in this muscle remain unknown.…”
mentioning
confidence: 99%